2012
DOI: 10.1007/s00294-012-0365-7
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genomes of two cockroaches, Blattella germanica and Periplaneta americana, and the phylogenetic position of termites

Abstract: The mitochondrial genomes are one of the most information-rich markers in phylogenetics. The relationships within superorder Dictyoptera have been debated in the literature. However, the closely related termites (Isoptera) are retained as unranked taxon within the order Blattaria (cockroaches). In this work, we sequenced the complete mitogenomes of two cockroaches, reconstructed the molecular phylogeny and attempted to infer the phylogenetic position of termites in Blattaria more reliably. The complete mtDNA n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 62 publications
3
27
0
Order By: Relevance
“…To date, complete mitogenome sequences of seven species from four families (Cryptocercidae, Blattidae, Blattellidae, and Polyphagidae) of the order Blattodea have been published (Yamauchi et al 2004;Zhang et al 2010;Cameron et al 2012;Xiao et al 2012;Chen 2013). We show phylogenetic relations among cockroach families based on the amino acid sequences derived from 13 mitochondrial protein-coding genes (PCGs) in the whole mitogenome.…”
Section: Introductionmentioning
confidence: 99%
“…To date, complete mitogenome sequences of seven species from four families (Cryptocercidae, Blattidae, Blattellidae, and Polyphagidae) of the order Blattodea have been published (Yamauchi et al 2004;Zhang et al 2010;Cameron et al 2012;Xiao et al 2012;Chen 2013). We show phylogenetic relations among cockroach families based on the amino acid sequences derived from 13 mitochondrial protein-coding genes (PCGs) in the whole mitogenome.…”
Section: Introductionmentioning
confidence: 99%
“…Inward and subsequent phylogenetic studies (Legendre et al 2008;Ware et al 2008;Cameron et al 2012;Djernaes et al 2012;Xiao et al 2012) have confirmed that the termites and the cockroach family Cryptocercidae are sister groups and that this clade is nested within the Blattodea. Since the termites had previously been classified as an order (Isoptera), a lower rank for this group was required.…”
Section: Introductionmentioning
confidence: 90%
“…The primers were designed from aligned conserved nucleotide sequences of Periplaneta americana [10] and Periplaneta fuliginosa [24]. Then, based on the obtained sequences, species-specific primers were designed using Primer Premier 5.0 to amplify the overlapping fragments.…”
Section: Methodsmentioning
confidence: 99%
“…Primers Nr1F and Pa1F were from Du et al [25]. Primers Nr9F, Nr9R, Nr10F, and Pa10F were from Xiao et al [10]. Within each PCR product, the full double-stranded sequence was determined by primer walking (PTC-100 thermal cycler, BioRad, Hercules, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation